Strategi Komunikasi dalam Meningkatkan Motivasi Kerja Pegawai di Masa Pandemi Covid-19 - Refika Mastanora; Melda Deswita (IAIN Batusangkar, 2021)
This paper discusses internal and external factors in increasing employee work motivation at the five people sub-district office during the Covid-19 pandemic. The type of research that researchers use is a type of research that is descriptive field research with a qualitative approach. The data collection technique used in this research is to use observation, interview and documentation techniques. The data analysis technique that the author uses in this study is in the form of data reduction, data presentation and conclusions or verification. The results of the research that the authors get are that the Communication Strategy in increasing Employee Work Motivation at the Lima Kaum Sub-District Office in the Covid-19 Pandemic Period is by monitoring and evaluating, holding meetings with employees at least once a month, establishing good relationships with employees, and completing needs. employees at work.